KAJIAN PERBANDINGAN PRODUKSI ASAP CAIR DARI TEMPURUNG SABUT KELAPA DAN TONGKOL JAGUNG1) - Stefy Wagiu; Dedie Tooy; Ruland Rantung (Universitas Sam Ratulangi, 2022)
ABSTRACTThis study aims to compare the quality of liquid smoke products using three raw materials,namely shell, coconut fiber and corn cobs. This research is expected to provide informationabout the manufacture of liquid smoke that is more efficient, so that it becomes the basis for thedevelopment of a more efficient liquid smoke maker in the future. Liquid smoke is a liquidsmoke vapor condensate resulting from the pyrolysis of wood. Phenolic compounds, carbonyland organic acids contained in liquid smoke play an important role as odor removers andrepellents. Thus it can be seen that the method of fumigation with liquid smoke can be easierand cheaper in plant care.This study used an experimental method and analyzed descriptively. The materials used in theprocess of making this liquid smoke were 90 kg shell, 90 kg coconut coir and 90 kg corn cob.Each treatment in the combustion process of making liquid smoke as much as 30 kg.Observations in this study were carried out from the comparison of raw materials to achieve thedesired liquid smoke results.From the results of the research, the yield of liquid smoke from the shell was 6.027 % 2. withthe performance of the tool 66.96%. The yield of corn cobs was 3,458% with the performanceof the tool 49.4 and the yield of the coconut coir was 2.964% with the performance of the tool49.4%. 3. With 30 kg of raw material for each shell, coconut coir and corn cobs require differentproduction times. The shell takes 9 hours, coconut coir 6 hours and corn cobs 7 hours.